Lobola and the Lost Offspring - Bontiya, Ndimphiwe (WritingThreeSixty: Journal or Research and Creative Text, 2018)
A private hospital room in Johannesburg. Mandisa is a 30 year-old engaged woman and a daughter to Sophie, a forty-nine year old woman. Mandisa is in a hospital bed when her mother enters the room escorted by a nurse.